Trauma to the permanent teeth - Feiglin Barry (Sciendo, 1985)
Trauma involves approximately 12% of endodontic problems, and the upper central incisor is the most common tooth involved. Great care must be taken in trying to ascertain the extent of the injury, the vitality of the pulp, the colour of the tooth and the on set of calcific obliteration of the pulp canal space. These are the keys to successful treatment should it be required. This applies equally well to enamel fractures right through to transverse root fractures and avulsion of teeth.